Sexual epigenetics: gender-specific methylation of a gene in the sex determining region of Populus balsamifera - Bräutigam, Katharina (Sci Rep, 2017)
Methylation has frequently been implicated in gender determination in plants. The recent discovery of the sex determining region (SDR) of balsam poplar, Populus balsamifera, pinpointed 13 genes with differentiated X and Y copies. We tested these genes for differential methylation using whole methylome sequencing of xylem tissue of multiple individuals grown under field conditions in two common gardens. The only SDR gene to show a marked pattern of gender-specific methylation is PbRR9, a member of the two component response regulator (type-A) gene family, involved in cytokinin signalling. It is an ortholog of Arabidopsis genes ARR16 and ARR17. The strongest patterns of differential methylation (mostly male-biased) are found in the putative promoter and the first intron. The 4th intron is strongly methylated in both sexes and the 5th intron is unmethylated in both sexes. Using a statistical learning algorithm we find that it is possible accurately to assign trees to gender using genome-wide methylation patterns alone. The strongest predictor is the region coincident with PbRR9, showing that this gene stands out against all genes in the genome in having the strongest sex-specific methylation pattern. We propose the hypothesis that PbRR9 has a direct, epigenetically mediated, role in poplar sex determination.